2011
DOI: 10.4314/mmj.v22i4.63945
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV and AIDS on the eldery: A case study of Chiladzulu district

Abstract: HIV may affect the elderly in a number of ways. They may become infected themselves; their children may suffer prolonged illness and incapacity, and need the elderly to look after them; the same children may then die from the illness, leaving the elderly without the support of the next generation; this bereavement also leaves the older people to meet funeral costs and then to take care of orphans left behind. HIV has impacts on old people in ways that are social , economic, psychological and physical in nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 1 publication
5
16
0
Order By: Relevance
“…Schatz et al [ 5 ] found that pensions for the elderly play a very important role in female-headed households affected by HIV and AIDS. However, in countries where there are no social pensions for older persons, the effect of HIV/AIDS is so intense that some have no alternative but to become beggars in order to make ends met [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schatz et al [ 5 ] found that pensions for the elderly play a very important role in female-headed households affected by HIV and AIDS. However, in countries where there are no social pensions for older persons, the effect of HIV/AIDS is so intense that some have no alternative but to become beggars in order to make ends met [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However the system may have come close to the breaking point, especially that increasingly older people e.g. grandparents have been taking responsibilities to raise orphans [6,59,60]. Seemingly with the worst situation over, hopefully the system will hold on and not break down.…”
Section: Discussionmentioning
confidence: 99%
“…Most OAs in South Africa (86%) reported that they were solely responsible for providing basic need for dependents . In Malawi, only 31% of OAs were dependent on adult children for help (Sefasi, 2010). In Kenya, social support was linked to increased pain and higher BMI scores (Ice, Heh, Yogo, & Juma, 2011;Wangui, 2009).…”
Section: Social Capitalmentioning
confidence: 99%